Brain Derived Neurotrophic Factor (BDNF) Gene in Peripheral Blood Cells of Stable Schizophrenia - Ku Zaifah, Assoc. Prof. Dr. Norsidah; Tokhi , Elham; Abd Rahim, Nour El Huda; A. Talib, Norlelawati; Mohd Noor, Hanisah (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: Epigenetic mechanisms regulate gene functions without causing a change in the nucleotide sequence of DNA. Brain-derived neurotrophic factor (BDNF) is a neurotrophin that regulates synaptic transmission and plasticity and has an essential role in neurodevelopment. Collected evidence suggests that epigenetic changes in the BDNF gene are related to the pathophysiology of psychiatric disorders such as schizophrenia. Therefore, the aim of this study was to assess the association of BDNF DNA methylation with schizophrenia. In addition, the relationship between BDNF DNA methylation and antipsychotics was studied. MATERIALS AND METHODS: Overall, 118 (88 male and 30 female) schizophrenia patients and 122 (92 male and 30 female) healthy controls were included in the study and methylation status was investigated using the Methylight Taqman® assay. RESULTS: There was no significant change in the DNA methylation status between schizophrenia patients and controls in this study despite its increased level (p=0.073). However, DNA methylation level was associated with sex and the difference was more significantly prominent in the male subjects (p=0.016). In addition, BDNF DNA methylation showed a positive significant correlation with the positive symptoms (p=0.032) of schizophrenia and antipsychotics use (p=0.013). CONCLUSION: The BDNF DNA methylation could be affected by gender and has a clinical association.